Awake craniotomy for glioma resection: Technical aspects and initial results in a single institution. (2nd November 2015) - Trimble, Gillian; McStravick, Clodagh; Farling, Peter; Megaw, Katie; McKinstry, Steven; Smyth, Graham; Law, Gillian; Courtney, Heather; Quigley, Gavin; Flannery, Thomas
Abstract : Introduction . Although variations in the technique of awake craniotomy (AC) have been widely reported, a key member of this interdisciplinary procedure is the healthcare professional performing assessments of neurological function during resection. The expertise of the latter will depend on the neurological function to be tested and on available resources of the institution. This report details our initial experience of an AC service utilizing the expertise of a speech and language therapist (SLT) and an experienced neuro-physiotherapist (NP) to monitor patient function during glioma resection. Methods . Forty-five patients underwent 50 AC procedures for eloquently located gliomas over a 3-year period. Patients with a glioma involving speech or sensorimotor areas were assessed preoperatively by the SLT/NP respectively. The same therapist monitored the patient's neurological function intraoperatively and executed a rehabilitation program tailored to the needs of the patient in the postoperative period. Results . Three patients underwent biopsy only, due to intraoperative seizures precluding intraoperative mapping (2 cases) or speech arrest on stimulation of a small recurrent tumor. The remaining 47 cases were suitable for repetitive neurological assessment "awake" during tumor debulking. One patient with a large sensorimotor tumor developed intraoperative hemiparesis due to outward brain herniation (which recovered postoperatively). Ten patients developed a new or worsened neurological deficit in the initial postoperative period (6 were detected intraoperatively), of which 5 eventually had resolution and returned to baseline function within 2 weeks. Conclusions . In our initial experience based anecdotally on a previous similar "non-awake" caseload, we have found AC with the input of the SLT/NP to be a key component in ensuring optimal functional outcomes for patients with gliomas in eloquently located areas.